Rhetorical & Persuasive Language: A Critical Discourse Analysis of Malala Yousafzai's Nobel Lecture - Altam, Saleh; Pathan, Mehrunnisa (South Asian Journal of Social Sciences and Humanities, 2021)
This paper makes an effort to present a Critical Discourse Analysis (CDA) of Malala Yousafzai’s Nobel peace prize lecture which was delivered on the 10th of December 2014 at the Oslo City Hall, Norway. More explicitly, the present research paper attempts to search concealed messages and ideologies that have been encrypted in Malala Yousafzai Nobel peace prize acceptance speech and how did she deliver her speech figuratively and persuasively. The techniques of collecting data were done by searching the transcript of Malala’s speech on the internet, interpreting it, retyping all the sentences which contained figurative and persuasive language, and coding data. The method makes use of Fairclough’s theory of critical discourse analysis that explicates ideology based on the text analysis, discourse practice, and sociocultural practice at the micro-level only. The speaker attains interaction and engagement with the addressees by means of using verbal expressions and figurative language in her speech. The paper discloses that Malala delivered her speech as a movement to defend girls’ education and women’s rights by using figurative and persuasive language. The finding displays that the ideology of Malala Yousafzai’s speech is women empowerment, girls’ education and giving quality education for all hegemonized and marginalized children of the oriental world.
Keywords: Critical Discourse Analysis; Malala Yousafzai; Nobel peace prize; Fairclough’s theory; girls’ education.